2003
DOI: 10.1073/pnas.1032913100
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated reduction of genes of oxidative metabolism in humans with insulin resistance and diabetes: Potential role of PGC1 and NRF1

Abstract: Type 2 diabetes mellitus (DM) is characterized by insulin resistance and pancreatic ␤ cell dysfunction. In high-risk subjects, the earliest detectable abnormality is insulin resistance in skeletal muscle. Impaired insulin-mediated signaling, gene expression, glycogen synthesis, and accumulation of intramyocellular triglycerides have all been linked with insulin resistance, but no specific defect responsible for insulin resistance and DM has been identified in humans. To identify genes potentially important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

89
1,542
17
19

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,787 publications
(1,682 citation statements)
references
References 55 publications
(41 reference statements)
89
1,542
17
19
Order By: Relevance
“…Consistent with this observation, we detected reduced expression levels of mitochondrial biogenesis marker genes cytochrome c, cytochrome c oxidase and mitochondrial transcription factor A 270 ( Figure 2C, and not shown). Moreover, investigations in non-diabetic but insulin resistant patients detected reduced expression rates of PGC-1α in muscle, correlating with reduced expression rates of mitochondria-associated genes (Mootha et al, 2003;Patti et al, 2003).…”
Section: Resultsmentioning
confidence: 94%
“…Consistent with this observation, we detected reduced expression levels of mitochondrial biogenesis marker genes cytochrome c, cytochrome c oxidase and mitochondrial transcription factor A 270 ( Figure 2C, and not shown). Moreover, investigations in non-diabetic but insulin resistant patients detected reduced expression rates of PGC-1α in muscle, correlating with reduced expression rates of mitochondria-associated genes (Mootha et al, 2003;Patti et al, 2003).…”
Section: Resultsmentioning
confidence: 94%
“…Heilbronn et al (13) have demonstrated that different biomarkers of mitochondrial biogenesis and metabolism are reduced in overweight and obese insulin-resistant subjects. Two other studies using cDNA microarrays have reported that mitochondrial metabolism in both muscle and adipocytes is disturbed in subjects with insulin resistance, type 2 diabetes and even in subjects with family history for diabetes (28,32). Both trials found a decrease in the expression of a subset of genes involved in mitochondrial oxidative metabolism, suggesting that impaired regulation of mitochondrial function could be an important mechanism linked to obesity and the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…Glycogen deficit may therefore be an early marker of dysfunctional metabolism in muscle of individuals prone to obesity-associated diabetes or perhaps an imprint left in the satellite cells of individuals who have had type 2 diabetes, despite reversal of clinical symptoms of the disease via weight loss. It has been previously shown that genes involved in oxidative metabolism and mitochondrial biogenesis are downregulated in skeletal muscle of individuals with type 2 diabetes, in individuals who are insulin-resistant and in healthy offspring of type 2 diabetes patients [16]. Functional impairment of skeletal muscle mitochondria has also been shown in these populations [18,44].…”
Section: Discussionmentioning
confidence: 99%
“…These may thus be diverted from the tricarboxylic acid cycle into other lipid metabolites such as ceramides, diacylglycerol and/or acylcarnitines, which in turn can interfere with the insulin signalling pathway [10,11], as discussed in reviews [12][13][14]. Indeed, decreased mitochondrial content and impaired oxidative capacity are correlated with insulin resistance and associated with obesity [15][16][17][18], but effects can be mitigated by weight loss and physical activity [19,20].…”
Section: Introductionmentioning
confidence: 99%